Titin founder mutation is a common cause of myofibrillar myopathy with early respiratory failure. Issue 3 (13th March 2013) - Pfeffer, Gerald; Barresi, Rita; Wilson, Ian J; Hardy, Steven A; Griffin, Helen; Hudson, Judith; Elliott, Hannah R; Ramesh, Aravind V; Radunovic, Aleksandar; Winer, John B; Vaidya, Sujit; Raman, Ashok; et al.
Abstract : Objective: Titin gene ( TTN ) mutations have been described in eight families with hereditary myopathy with early respiratory failure (HMERF). Some of the original patients had features resembling myofibrillar myopathy (MFM), arguing that TTN mutations could be a much more common cause of inherited muscle disease, especially in presence of early respiratory involvement. Methods: We studied 127 undiagnosed patients with clinical presentation compatible with MFM. Sanger sequencing for the two previously described TTN mutations in HMERF (p.C30071R in the 119th fibronectin-3 (FN3) domain, and p.R32450W in the kinase domain) was performed in all patients. Patients with mutations had detailed review of their clinical records, muscle MRI findings and muscle pathology. Results: We identified five new families with the p.C30071R mutation who were clinically similar to previously reported cases, and muscle pathology demonstrated diagnostic features of MFM. Two further families had novel variants in the 119th FN3 domain (p.P30091L and p.N30145K). No patients were identified with mutations at position p.32450. Conclusions: Mutations in TTN are a cause of MFM, and titinopathy is more common than previously thought. The finding of the p.C30071R mutation in 3.9% of our study population is likely due to a British founder effect. The occurrence of novel FN3 domain variants, although still of uncertain pathogenicity, suggests that other mutations in this domain may cause MFM, and that the disease is likely to be globally distributed. We suggest that HMERF due to mutations in the TTN gene be nosologically classified as MFM-titinopathy.